Conductivity fluctuations in proton-implanted ZnO microwires. (16th June 2016) - Dolgin, B; Lorite, I; Kumar, Y; Esquinazi, P; Jung, G; Straube, B; Heluani, S Perez de
Abstract: Electric noise can be an important limitation for applications of conducting elements in the nanometer size range. The intrinsic electrical noise of prospective materials for opto-spintronics applications like ZnO has not yet been characterized. In this study, we have investigated the conductivity fluctuations in 10 nm thick current paths produced by proton implantation of ZnO microwires at room temperature. The voltage noise under a constant dc current bias in undoped, as well as in Li-doped microwires, is characterized by 1 / f a power spectra with a ∼ 1 . The noise intensity scales with the square of the bias current pointing to bias-independent resistivity fluctuations as a source of the observed noise. The normalized power spectral density appears inversely proportional to the number of carriers in the probed sample volume, in agreement with the phenomenological Hooge law. For the proton-implanted ZnO microwire and at 1 Hz we obtain a normalized power spectral density as low as ∼ 10 − 11 Hz −1 .